The curse - Kenyon, Sherrilyn (Pocket Books urban fantasy, 2012)
With the freedom of an entire race hanging in the balance, Evalle has two days to make good on a promise that she suddenly has no hope of fulfilling when demonic Svart Trolls invade Atlanta. She takes a leap of faith, seeking help from the one man who recently put Evalle in his cross hairs--Black Ops specialist Isak Nyght. While trying to stop the bloody troll-led gang wars, Evalle unwittingly exposes a secret that endangers all she holds dear, and complicates her already tumultuous love life with the mysterious Skinwalker, Storm. But when Evalle discovers she's the number one target in the Medb coven's ruthless plan to destroy all Beladors, the deadly Alterant is forced to make a game-changing decision with no time left on the clock.